Controllability of Radial Magnetic Bearing. (2016) - Shelke, Santosh
Abstract: The magnetic bearing works on the principle of magnetic levitation. Integration of the geometric and control designs is the current trend in mechatronic products. Conventionally, in control of rotors in the vertical direction, it must be supported at two places by radial magnetic bearings. A thrust magnetic bearing is also provided to prevent axial movement of the shaft. In the present work, control design methodology of four pole pair active magnetic bearings has been proposed. This work is dealing with the modeling, investigations and controlling of radial magnetic bearing system. Considerations based on the four pole pair's model with switched mode power supply. Investigations of radial forces in two axes model and performance response are carried out through the PID controller system. The response is presented for standstill and dynamic conditions using the implemented Simulink software. Simulation results showed that rotor is in standstill position with constant air gap of 1 mm. This validates bearing design dimensions and system parameters designed for control of four pole pair radial magnetic bearing considering 1 mm air gap length.